2021
DOI: 10.3389/fcell.2021.777258
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Epigenetics of Diabetic Cardiomyopathy in Type 2 Diabetes

Abstract: Diabetic cardiomyopathy (DCM) is characterized by diastolic relaxation abnormalities in its initial stages and by clinical heart failure (HF) without dyslipidemia, hypertension, and coronary artery disease in its last stages. DCM contributes to the high mortality and morbidity rates observed in diabetic populations. Diabetes is a polygenic, heritable, and complex condition that is exacerbated by environmental factors. Recent studies have demonstrated that epigenetics directly or indirectly contribute to pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…Several cases of hypermethylation or demethylation, histone modifications, and altered expression of noncoding RNA associated with diabetic cardiomyopathy in diabetic patients or rodents have been reported and reviewed elsewhere [ 169 , 170 , 171 ]. Here, we summarize the recent progress with therapeutic potential.…”
Section: Molecular Mechanism Of Diabetic Cardiomyopathymentioning
confidence: 99%
“…Several cases of hypermethylation or demethylation, histone modifications, and altered expression of noncoding RNA associated with diabetic cardiomyopathy in diabetic patients or rodents have been reported and reviewed elsewhere [ 169 , 170 , 171 ]. Here, we summarize the recent progress with therapeutic potential.…”
Section: Molecular Mechanism Of Diabetic Cardiomyopathymentioning
confidence: 99%
“…Over 70% of individuals with diabetes will develop some form of heart disease, such as acute coronary syndrome, during their lifespan (161). It is estimated that 12% of patients with diabetes eventually develop severe heart failure (HF) and often die due to DCM (162,163). Recent studies demonstrated that diabetes could increase the risk of HF 2-3 times and increase the death rate of HF by 2.5 times in individuals with diabetes compared with control individuals (164).…”
Section: The Role Of Epitranscriptomics In Diabetic Cardiomyopathymentioning
confidence: 99%
“…So, it has been proposed that the balance between histone acetylation and deacetylation must be tightly regulated (114). Hence, epigenetics in cardiovascular research and therapy is an exciting and promising emerging research field (115).…”
Section: Role Of Epigenetics In Diabetic Hfmentioning
confidence: 99%